Convergent gut microbiome adaptation and pervasive antibiotic resistome in Qinghai–Tibet Plateau passerines - Shi, Shunan; Qi, Jiancheng; Peng, Wenxuan; Su, Xiaodong; Chen, Peng; Xu, Shoubiao; Li, Sheng; Ma, Long; Wang, Wenlong; Jiang, Ke; Liu, Zhiguo; Li, Wei; et al. (Frontiers in Microbiology, 2026)
IntroductionThe Qinghai-Tibet Plateau, an extreme high-altitude ecosystem, presents a unique model for studying host-microbe-environment coevolution under environmental stress. However, the role of resident wildlife, particularly non-migratory passerines, as reservoirs and vectors for cross-boundary antibiotic resistance gene (ARG) dissemination remains poorly understood.MethodsHere, through metagenomic analysis of two endemic passerines (Pseudopodoces humilis and Pyrgilauda ruficollis) and their habitats.ResultsWe reveal convergent adaptations in their gut microbiomes, dominated by Actinomycetota, Pseudomonadota and Bacillota. Functional enrichment in carbohydrate metabolism and genetic information processing underpins host energy optimization in extreme high-altitude environments. Critically, these birds constitute a major reservoir of ARGs, harboring 153 antibiotic resistance ontologies (AROs) with nearly universal resistance to clinical antibiotic classes. The core resistome—comprising glycopeptide (van clusters), fluoroquinolone, and tetracycline resistance genes—reflects anthropogenic contamination amplified by environmental persistence. Environmental transmission pathways were unequivocally demonstrated via 47 AROs shared between avian hosts and proximal matrices (soil/grass), coupled with livestock-derived antibiotic influx through excreta, establishing the plateau as a hotspot for resistance gene flux. Strikingly, “low-abundance–high-resistance” taxa (Pseudomonadota, Actinomycetota, and Bacillota; ≤30% abundance but >80% ARG contribution) drive resistome plasticity, potentially facilitated by horizontal gene transfer.DiscussionOur findings redefine resident passerines as sentinels of ecosystem health and bridges for cross-boundary antimicrobial resistance (AMR) spread. Mitigating global AMR thus necessitates interdisciplinary strategies targeting environmental reservoirs (e.g., regulating livestock antibiotic use) and monitoring avian-mediated gene flow.